Transforming Ethnopedagogic-Based Learning of Maluku History to Improve Student Understanding and Engagement - Johan Pattiasina; Sem Touwe; Paisal Ansiska (STAI Hubbulwathan Duri, 2025)
History education is crucial in shaping students’ cultural identity and historical awareness. However, conventional memorization-based methods often fail to enhance students’ understanding and engagement, especially in regional contexts such as Maluku. Although previous studies have discussed the theoretical value of ethnopedagogics, empirical research on its effectiveness in regional history education remains limited. This study addresses that gap by evaluating an ethnopedagogic approach integrating local cultural values into history learning. Using a quasi-experimental design without a control group, the study involved 120 high school students in Ambon City. Data were collected through historical comprehension tests, classroom observations, and interviews. Paired t-tests measured changes in historical understanding, while ANOVA analyzed behavioural, emotional, and cognitive engagement differences. Results showed statistically significant improvements: comprehension scores increased from a pre-test mean of 57.5 (SD = 4.2) to a post-test mean of 77.5 (SD = 3.8) (t(119) = 4.32, p = 0.002), and engagement indicators improved significantly (F(2,118) = 5.21, p = 0.001). These findings provide empirical evidence supporting the integration of ethnopedagogic methods into Indonesia’s history curriculum. The study highlights how culture-based, experiential learning enhances student engagement, fosters critical understanding, and strengthens cultural identity. Further research with broader and comparative designs is recommended.